2004
DOI: 10.1111/j.1471-0528.2004.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

WHO multinational study of three misoprostol regimens after mifepristone for early medical abortion.

Abstract: Objectives To compare the side effect profiles of regimens of oral and vaginal administration of misoprostol after a single oral dose of 200 mg of mifepristone and to investigate patients' perceptions of medical abortion. Design Double-blind, randomised controlled trial.Setting Fifteen gynaecological clinics in 11 countries.Population A total of 2219 healthy pregnant women requesting medical abortion with 63 days of amenorrhoea. Two thousand women were asked about their perceptions of the method. Methods Mifep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 19 publications
2
33
1
4
Order By: Relevance
“…42 In studies that compared 600 mcg oral misoprostol to MVA for treatment of incomplete abortion, cramping was reported by 56 to 95 percent, nausea and vomiting by 5 to 33 percent, chills by 5 and 85 percent, fever by 0.4 to 2 percent, and fever/chills by 3.8 and 15% of women. 9,10,13,19,41 Cramping generally starts within the first few hours but may begin as early as 10 minutes after misoprostol administration.…”
Section: Side Effects After Misoprostol 11mentioning
confidence: 99%
See 1 more Smart Citation
“…42 In studies that compared 600 mcg oral misoprostol to MVA for treatment of incomplete abortion, cramping was reported by 56 to 95 percent, nausea and vomiting by 5 to 33 percent, chills by 5 and 85 percent, fever by 0.4 to 2 percent, and fever/chills by 3.8 and 15% of women. 9,10,13,19,41 Cramping generally starts within the first few hours but may begin as early as 10 minutes after misoprostol administration.…”
Section: Side Effects After Misoprostol 11mentioning
confidence: 99%
“…This effect has not been reported in the literature on misoprostol for treatment of incomplete abortion but has been reported in relation to the drug's use for medical abortion and as well as other indications. 42 If rash occurs, no intervention is needed but in the event of skin irritation, an antihistamine, such as Benadryl®, can be provided.…”
Section: Side Effects After Misoprostol 11mentioning
confidence: 99%
“…Studies on early MTOP have consistently shown that procedure failure and more pain and bleeding than expected are predictors of not choosing MTOP again. 24,[87][88][89] The likelihood of each of these predictors increases with gestational age. 15,89 Of particular relevance is the increase in need for surgical evacuation following MTOP because of ongoing pregnancy or missed/incomplete abortion, which has been reported to increase from 0.9% at 9-10 weeks to 7.9% at 12-13 weeks of pregnancy.…”
Section: Acceptabilitymentioning
confidence: 99%
“…18,20,88,102 The incidence and severity of symptoms is influenced by the dose and route of administration of misoprostol; 88 gastrointestinal symptoms and fever are more common with oral administration. 88 We found that a similar proportion of women (~ 22%) having MTOP and STOP were still bleeding 2 weeks after the procedure, although more women in the MTOP group reported heavy blood loss. Duration of bleeding has consistently been reported to be longer after MTOP than STOP and longer after abortion at 10-13 weeks compared with abortion at ≤ 9 weeks.…”
Section: Side Effectsmentioning
confidence: 99%
“…Information on LTFU rates in medical abortion literature are derived from clinical trials and are highly variable due to differences in medication administration protocol, follow-up methods and timing, patient population and laws, as well as whether the data were collected prospectively or retrospectively. Most clinical trials report LTFU rates below 5% [6,[11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%